Feline tuberculosis caused by Mycobacterium bovis infection of domestic UK cats associated with feeding a commercial raw food diet. Issue 4 (7th November 2020) - O'Halloran, Conor; Tørnqvist‐Johnsen, Camilla; Woods, Glynn; Mitchell, Jordan; Reed, Nicki; Burr, Paul; Gascoyne‐Binzi, Deborah; Wegg, Michaela; Beardall, Sarah; Hope, Jayne; Gunn‐Moore, Danièlle
Abstract: Mycobacterium (M.) bovis can infect cats and is a demonstrated zoonosis. We describe an outbreak of M. bovis in pet cats across England and Scotland associated with feeding a commercial raw food diet. Forty‐seven cats presented with (pyo)granulomatous lesions, lymphadenopathy, pulmonary and/or alimentary disease over a one‐year period where M. bovis infection was suspected or definitively diagnosed, and the cats all consumed the same specific brand of commercial raw venison pet food. Infection with M. bovis genotype 10:a was confirmed by culture and DNA typing of isolates in a small number of cases ( n  = 5); PCR was used in combination with or as an alternative to culture ( n  = 12) and/or infection with a Mycobacterium tuberculosis complex group organism was strongly suggested by positive responses to an interferon‐gamma release assay (IGRA; n  = 34). Asymptomatic at‐risk cats were screened by IGRA, identifying a further 83 infected cats. The five culture‐positive cases were distributed across areas of England and Scotland at low risk of endemic bovine tuberculosis. Investigations revealed affected cats were mainly indoor‐only, and had been fed the same commercial raw food as at least part of their diet. This diet was recalled by the manufacturer due to failure of statutory meat inspection of the component venison. As far as possible, other sources of infection were explored and excluded, including wildlife contact, access to raw milk and living with people with active M. bovis infection. Four owners and one veterinary surgeon were found to have high likelihood of latent tuberculosis infection. One owner required treatment. Although it was not possible to conclusively demonstrate a zoonotic origin for these infections, neither was it possible to eliminate the possibility. Our results provide compelling evidence that the commercial raw diet of these cats was the likely route of M. bovis infection in this outbreak of cases.